What is the answer to x+9=18-2x?

i am just 13, therefore cannot succeed more complex than it’s. In addition show work please.

3x + 9 = 18
3x = 9
x = 3
————–
-2x + 6 = -2
-2x = -8
x = 4
—————
14x – 12 = 114
14x = 126
x = 9
Almost, you really need to go every one of the x’s up to one part and all sorts of associated with the figures to another.

2x+6=4x-2
6=2x-2
8=2x
4=x
17x-12=114+3x
17x=126+3x
14x=126
X= 126/14
X=9
X+9=18+2x
9=18+x
-9=x

x+9=18-2x
x+2x=18-9
3x=9 /3
x=3
2x+6=4x-2
2x-4x=-2-6
-2x=-8 /(-2)
x=4
17x-12=114+3x
17x-3x=114+12
14x=126 /14
x=9

x+9=18-2x
-9 -9
+2x +2x
3x=9
x=9/3 or 3
2x+6=4x-2
+2 +2
-2x -2x
8=2x
x= 8/2 or 4
17x-12=114+3x
+12 +12
-3x -3x
14x = 126
x= 126/14 or 9

2x+6=4x+2
4=2X
x=2
17x-12=114+3x
14x=126
x=9

Answer 6

You need to use the ” replace the part, replace the indication guideline” . X+9=18-2x would be x=18-2x – 9 which would be 3x = 9 ( because in the event that you place the minus on the other hand it becomes the contrary that is good and x +2x = 3x) therefore x= 3 because 9 /3 is 3 . 2 x+6= 4x-2 would be -2x=-4 therefore x=-2. I cannot perform some final one given that it’s very difficult and I also believe you really need to about try to comprehend it cos or else you’ll never ever obtain it.
I am sorry should this be no assistance but I am of low quality at outlining maths all the best

Answer 7

Include 2x towards x and acquire 3x+9=18, subtract 9 from 18 and acquire 3x=9, the divide 9 by 3x and acquire X=3. 2nd concern, subtract subtract 2x from 4x and acquire 6=2x-2, adding 2 towards 6 and acquire 8=2x, after that divide 8 by 2x and you also have x=4. 3rd concern, include 12 to 114 and acquire 17x=126+3x, after that subtract 3x from 17x and acquire 14x=126, after that divide 126 by 14x, and you also have x =9.

x+9=18-2x
Include 2x to both edges associated with the equation. This can block out the bad 2x on right-side so that you tend to be remaining with 3x+9=18. You need to try to possess x alone therefore subtract the 9 from both edges. This can make you with 3x=9. Today divide by 3. Therefore x=3

Leave a Comment